Evaluating the Accuracy of Determining Coordinates of Corners of the Building Surveyed in Tilt Technology - Pirti, Atinc; Yucel, Mehmet Ali (ELSEVIER, 2023)
Integrated Inertial Measurement Unit (IMU) and electronic compass; small, sturdy form factor; supports all communications, satellites, and constellations (Revolutionary 9 axis IMU and ultra-compact 3-axis e-Compass). By integrating a 9-axis IMU with a digital compass, the Topcon Hiper Versatile Global Navigation Satellite System (VR GNSS) receiver can correct for up to 15 degrees of pole tilt. It may be now measured all the way to the edge/corner of a building without requiring an offset. The emerging technology makes up for the fact that plum field surveys can be off by up to 15 degrees. The accuracy of measured building corners is investigated in this study using Topcon Inertial Levelling Technology (TILT) in the IMU and e-Compass. The results of a case study of 5, 10, 15 degree tilt angles show that a 3D positioning accuracy of about 10 cm is achievable even when the pole is tilted.
Keywords: TILT; GNSS; Accuracy; Precision; Corners of the building; Engineering